1996
DOI: 10.1159/000218002
|View full text |Cite
|
Sign up to set email alerts
|

Hybridomas Reveal Shared Immunodominant Epitopes of γ-Glutamyltransferase Isoforms from Human Kidney and Renal Cell Carcinoma

Abstract: Metastatic renal cell carcinoma (RCC) is a tumor with a poor prognosis resistant to chemotherapy and irradiation. However, in rare cases, spontaneous regressions of metastases after nephrectomy have been reported that were ascribed to destruction of the tumor by the immune system. In earlier studies, we and others identified the expression of modified antigens in RCC. In particular, a concanavalin A-binding isoform of γ-glutamyltrans-ferase (γGT) comprises about 50% of the enzymatic activity found in the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…These surfaces are usually not connected to the circulation. In contrast, GGT is expressed over the entire cell surface in RCC ( Fischer and Scherberich, 1996 ; Kaufmann et al , 1997 ) and is therefore accessible through the circulation. This may subsequently lead to elevated serum levels of GGT and higher intracellular levels of GSH ( Lusini et al , 2001 ), which correlate with the tumour burden.…”
Section: Discussionmentioning
confidence: 99%
“…These surfaces are usually not connected to the circulation. In contrast, GGT is expressed over the entire cell surface in RCC ( Fischer and Scherberich, 1996 ; Kaufmann et al , 1997 ) and is therefore accessible through the circulation. This may subsequently lead to elevated serum levels of GGT and higher intracellular levels of GSH ( Lusini et al , 2001 ), which correlate with the tumour burden.…”
Section: Discussionmentioning
confidence: 99%
“…8) and would therefore not be accessible to mAb 138H11 in circulation. This was demonstrated earlier in an extracorporeal perfusion model with human tumourbearing kidneys when 99m Tc-labelled mAb 138H11 was up to 20-fold enriched in the tumour compared to normal tissue [16][17][18] .…”
Section: Discussionmentioning
confidence: 65%
“…Accumulating evidence has suggested that GGT is deregulated in cancer cells and could reflect tumor progression and aggressiveness [ 20 ]. Although GGT is limited to the brush border membrane of proximal tubules of the normal kidney tissues, it has been confirmed that GGT is expressed extensively on the membrane of RCC cells [ 21 , 22 ]. As a membrane-bound enzyme, GGT plays a substantial role in sustaining the production of intracellular glutathione (GSH), which can function as an important antioxidant to protect cells from reactive oxygen compounds and free radicals.…”
Section: Discussionmentioning
confidence: 99%